Design of an underwater robot manipulator for a telerobotic system. Issue 6 (September 2013) - Cobos-Guzman, Salvador; Torres, Jorge; Lozano, Rogelio
SUMMARY This paper describes a telerobotic system used for manipulation tasks in underwater environments. The telerobotic system is composed of a robotic arm of 3 degrees of freedom. This robotic arm has been designed to support corrosion environments such as seawater or freshwater. The prototype is designed to support several types of perturbations such as ocean currents and high pressures. The main objective is to efficiently control a teleoperation task considering common perturbations present in deep water. Finally, this paper presents the design, modelling and experiments of the underwater telerobotic system.